SEWAGE BLOCKAGE DETECTION AND MONITORING SYSTEM USING IOT - Rajendra Kulkarni; Aditya Chekki; Biradar Dnyaneshwar; Karan (International Educational Journal of Science and Engineering, 2026)
Sewage blockage is a critical issue that leads to urban flooding, contamination, and environmental hazards. Traditional inspection methods are labor-intensive and hazardous, requiring workers to manually check and clear blockages. Monitoring the drainage system is essential to maintaining the cleanliness and health of the city. Due to the incompetence of manual monitoring, drainage issues are handled slowly and take longer to resolve. The system uses a wireless sensor network made up of sensor nodes to mitigate all of these problems. The suggested system is a real-time, IoT-based, low-maintenance system that sends a message to the managing station if a manhole breaches a set of threshold values. In addition to helping the public, this technology lowers the risk of mortality for manual scavengers who clean the subterranean drainage system. This smart robotic system reduces human intervention, enhances safety, and improves maintenance efficiency. The combination of IoT, robotics makes it a cost- effective solution for urban drainage management. Sewage Blockage Detection System that uses a four-wheeled robotic vehicle equipped with ESP32-CAM for real-time video surveillance, ultrasonic and IR sensors for obstacle detection, and gas sensors for hazardous gas monitoring. The system is controlled by Node MCU ESP8266, which processes data and transmits it to a Blynk IoT app or a local web server for remote monitoring. A high-pressure jet system is integrated to clear minor blockages autonomously.